The promise of PD1/PDL1 targeted immunotherapy in locally advanced cervical cancer: a game-changer for patients outcome? - Fadila Kouhen; Fadila Kouhen; Fadila Kouhen; Adil El Ghanmi; Adil El Ghanmi; Hanane Inghaoun; Hayat Miftah; Bouchra Ghazi; Bouchra Ghazi; Abdallah Badou (Frontiers in Immunology)
Locally advanced cervical cancer remains a significant therapeutic challenge, with high rates of recurrence and metastasis despite advances in chemoradiation. Immunotherapy, particularly immune checkpoint inhibitors targeting the PD-1/PD-L1 axis, has emerged as a promising strategy to enhance treatment efficacy. This review explores the integration of immunotherapy with standard chemoradiation, highlighting the potential of PD-1 inhibitors, such as pembrolizumab, in improving progression-free survival (PFS) among high-risk patients. Furthermore, the role of predictive biomarkers, including microsatellite instability (MSI) and tumor mutational burden (TMB), is examined to refine patient selection and personalize therapeutic approaches. Emerging strategies, including the use of nivolumab, ipilimumab, and maintenance immunotherapy, are also discussed. While preliminary clinical data are encouraging, further research is required to optimize treatment combinations, establish robust patient selection criteria, and enhance long-term outcomes in cervical cancer management.